HUMAN RESOURCE SCORECARD DALAM PENDIDIKAN NONFORMAL DAN INFORMAL - Widya Ayu Puspita (JIV-Jurnal Ilmiah Visi, 2008)
Human resource scorecard is a tool to record human resource performance in a card system, by focusing on long and short term and using financial and non financial indicators. There are four perspectives in this approach, which are learning and growth, internal business process, customer and finance. Human resource scorecard is not only a tactic measurement but a strategic management to manage long term strategies. This articles discusses how human resource scorecard can be implemented in the formal and nonformal organization comprehensively to increase human resource quality and to improve education organization, so that, it can give the best service to community.